2007
DOI: 10.1016/j.cognition.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

It’s the way that you, er, say it: Hesitations in speech affect language comprehension

Abstract: Everyday speech is littered with disfluency, often correlated with the production of less predictable words (e.g., Beattie & Butterworth [Beattie, G., & Butterworth, B. (1979). Contextual probability and word frequency as determinants of pauses in spontaneous speech. Language and Speech, 22,[201][202][203][204][205][206][207][208][209][210][211]). But what are the effects of disfluency on listeners? In an ERP experiment which compared fluent to disfluent utterances, we established an N400 effect for unpredicta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(204 citation statements)
references
References 20 publications
11
187
5
1
Order By: Relevance
“…Hahne and Friederici (2001) A possible caveat of this study is that longer sentence and critical word durations during foreign-accented speech, compared to native speech, might have affected language comprehension. Previous literature on hesitations in speech (which, by definition, make sentences last longer) has shown that when target words are preceded by a hesitation, the N400 effect for unpredictable vs. predictable words is reduced (compared to fluent utterances; Corley et al, 2007). In our study, the duration of sentences and critical words was longer in the foreign than in the native condition, and this might have led to a reduction in the magnitude of the semantic gradient for the foreign accents.…”
Section: Discussionmentioning
confidence: 99%
“…Hahne and Friederici (2001) A possible caveat of this study is that longer sentence and critical word durations during foreign-accented speech, compared to native speech, might have affected language comprehension. Previous literature on hesitations in speech (which, by definition, make sentences last longer) has shown that when target words are preceded by a hesitation, the N400 effect for unpredictable vs. predictable words is reduced (compared to fluent utterances; Corley et al, 2007). In our study, the duration of sentences and critical words was longer in the foreign than in the native condition, and this might have led to a reduction in the magnitude of the semantic gradient for the foreign accents.…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli were 160 highly constrained fluent and disfluent utterances ending in predictable (cloze probability 0.84, range 0.52-1) or unpredictable (cloze probability 0) target words and were based on those used in Corley et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Because disfluency tends to precede less predictable items in speech (Beattie and Butterworth, 1979) we hypothesised that the semantic integration disadvantage for unpredictable items would diminish post-disfluency, resulting in a smaller N400 difference between unpredictable and predictable target words following repetitions. Because disfluency affects attention (Collard et al, 2008) we expected target words to be more likely to be recognised if they had been initially encountered post-disfluency (Collard et al, 2008;Corley et al, 2007).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations